Serum Procalcitonin Guided Antibiotic Therapy in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Khanam, Rawshan Arra; Haque, Md Ashraful; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2015)
Chronic obstructive pulmonary disease (COPD) is a preventable and treatable, but progressive disease. Hospital admissions of patients with COPD are frequently due to acute exacerbations of COPD (AECOPD). AECOPD are very common, affecting about 20% of COPD patients. The bacterial infection plays an important role in the exacerbation of COPD patients. In addition, recent studies using molecular diagnostics indicate that a substantial proportion of AECOPD are associated with viral infection. Accurate methods to differentiate viral and bacterial respiratory infections to allow targeted antibiotic therapy would be beneficial. Acute phase reactants are capable of demonstrating the inflammation; however, they cannot be employed to make a difference between bacterial and nonbacterial causes of the inflammation. Recently, measurement of procalcitonin (PCT) levels appears to be useful in order to minimize this problem. Bangladesh Crit Care J September 2015; 3 (2): 67-70